2017
DOI: 10.5296/ijl.v9i2.10811
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Adjective Types and Functions in Popular Science Articles

Abstract: This study aims to analyze adjective types and functions found in popular science articles. 25 articles were randomly selected to analyze by employing the conceptual framework of adjective types in English by Khamying (2007). The findings reveal that ten types of adjectives including descriptive, proper, quantitative, numeral, demonstrative, possessive, distributive, emphasizing, exclamatory, and relative were found in the articles. The first five ranks of adjective types, which frequently used were hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Researcher Jutharat Jitpranee identifies that one of the most important principle in populas science materials is the availability and interesting presenting of the information (Jitpranee, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Researcher Jutharat Jitpranee identifies that one of the most important principle in populas science materials is the availability and interesting presenting of the information (Jitpranee, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Adjective plays a crucial role in describing and/or modifying nouns by attributing and qualifying them (Jitpranee, 2017;Khamying, 2007). However, in his study on English adjectives in online comments of Algerian English speakers, Belfarhi (2019) discovered that adjectives are used in different forms by combining them with non-linguistics forms (emoji) and how they did not function as a modifier to nouns.…”
Section: Previous Studies On Adjective In Online Contentmentioning
confidence: 99%
“…Adjectives also work as a persuasive method by describing the characteristic of something or someone. Unlike research papers, adjectives are used in popular science articles to mainly express scientific knowledge to readers as the meaningfulness of the articles depends on how attractive, readable, and accessible they are (Jitpranee, 2017). However, Marzá (2011), through her corpus analysis of adjectives in hotel advertisements, discovered that unlike the common belief of advertisements contains high use of the adjective, hotel advertisements use a subtle amount of adjective as it is discovered that evaluative adjective is not even half the number of adjective in the corpus.…”
Section: Previous Studies On Adjective In Online Contentmentioning
confidence: 99%
“…This study found that the use of adjectives connected to the framing of the certain cases. In these views (Altun, 2019;Durán-Muñoz, 2019;Edo Marzá, 2017;Fragaki, 2010;Jing, 2011;Jitpranee, 2017;Kartal, 2017;Marzá, 2013;Mazdayasna & Firouzi, 2013;Mia, 2018;Nashina, 2010;Salim & Saad, 2016;Tran, 2013) revealed that the adjectives could show the condition, situation or even the characteristics of the objects. This study also agreed that the adjectives could be used for imaging the object and it also could be used for evaluating the object.…”
Section: Numeral Adjectivementioning
confidence: 99%
“…Corpus could be used to figure out the Greek adjective (Fragaki, 2010). To figure out the most frequent adjective in the academic writing, such as social sciences, technology, medical sciences, linguistics, literature and technical by applying corpus (Ağçam & Özkan, 2015;Jitpranee, 2017;Kartal, 2017;Mazdayasna & Firouzi, 2013;Nashina, 2010). Those previous studies used corpus to investigate the most frequent adjective on the other hand, and those studies only observed the quantity and type of the most frequent adjective.…”
Section: Introductionmentioning
confidence: 99%